The impact of digital health marketing ads on tourism in Jordan - Mazuri, Abd Ghani; Mahmood, Alghizzawi; Mohammed, Habes (2021)
The Corona virus spread in the Chinese province at first, then quickly moved to the rest of the world, claiming the lives of many, burdening many patients, its future course became dangerous at all levels and fields, and its impact reached global. It affected health, social and economic sector. As the Corona virus is one of the most dangerous respiratory diseases that humanity is exposed to, due to the speed of its transmission between individuals and its effect on the lungs as life activities are not as normal as they were before. This leads to material and moral harm to humanity as a whole even after the discovery of the vaccine. This virus continues to be a challenge for many sectors, especially tourism which is an important driver of the workforce and economic dynamics in many Countries . This study aims to shed light on the challenges facing the tourism sector in Jordan. With the aim of reaching future plans capable of reviving this sector to face the challenges caused by Corona by measuring the impact of digital awareness announcements on the commitment of tourists to implement health safety instructions related to the Coronavirus. In order to achieve the objectives of the study, a study model was proposed, and then an electronic research survey was conducted for decision-makers in the tourism establishments. Accordingly, 100 questionnaires were distributed and 92 valid questionnaires were retrieved for the purposes of analysis and study on the basis of the structure. Equation modeling (SEM). When analyzing the data, the results showed that health advertisements and educational advertisements have a positive impact on digital advertisements, which in turn raise awareness and health protection for tourists through their commitment to health instructions during their visits to tourist sites and their practice of entertainment programs, and activities. As digital media plays an important role in the lives of individuals as it is the main information key for all individuals, which strengthens its role in spreading awareness of the Coronavirus, and this has been confirmed by the World Health Organization about the role of digital media in quickly reaching the public with regard to any important information to protect them. Therefore, digital advertising is considered to have the greatest impact in creating health awareness about this virus, and therefore this study confirms through the proposed model that deals with educational and health advertisements through digital media, that there is an important impact of digital advertising on the awareness and health sectors in creating protection from this virus among tourists, by making sure that health instructions are applied in the required manner that provides them with protection. There are many studies dealt with tourism promotion in Jordan, and the factors that help in encouraging tourism in Jordan in light of the Coronavirus have been discussed to provide a helping hand to decision-makers in the tourism sector to comprehensively understand the factors that affect individuals, by encouraging them to undertake tourist tours in light of The Corona pandemic. Through the perceptions of the study results, we recommend more future studies dealing with the marketing of digital health advertisements to increase awareness among tourists, which will ensure the reopening of the tourism sectors and alleviate the general health crisis in the sectors affected by closures. Despite the scientific contribution to this research, it suffers from some limitations, represented in the fact that the study is limited in Jordan only. It is possible if it was conducted in other countries with different terrain. There may be more comprehensive contributions, in addition to the fact that this study was conducted in a crisis, which may give some indications that are possible To be different in a normal situation.